Inovasi Pangan Lokal Berbasis Kearifan Pertanian: Analisis Location Quotient Dan Swot Untuk Pengembangan Permen Tomat Di Kabupaten Bandung Dan Kecamatan Pangalengan - Manik, Gia Cinta Saria; Pohan, Malvira; Hanum, Sayidah Latifah; Darma, Sernanda Putri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to explore the possibility of developing processed tomato products in the form of jelly candy as a local food innovation derived from agricultural wisdom in Pangalengan District, Bandung Regency. The main problem faced by tomato farmers is post-harvest losses due to tomatoes being easily frozen and the selling price being unaffordable. Therefore, product innovation in the form of tomato jelly candy is designed to add value, extend shelf life, and open up new business opportunities for the local community. The method used in this study is a mixed approach with quantitative analysis using Location Quotient (LQ) and qualitative analysis through interviews and SWOT analysis. The research findings reveal that tomatoes are a major commodity with an LQ value of 1.615, indicating potential for export and surplus in production. The SWOT analysis identifies advantages in terms of nutritional content and product texture, broad market opportunities, and challenges related to product durability and competition in the market. These results explain that with an approach based on local wisdom and the right development strategy, tomato jelly candy has the potential to become a superior agro-industrial product and support food security and the regional economy in a sustainable manner.